Large Variations in N2O Fluxes from Bioenergy Crops According to Management Practices and Crop Type - Fabien Ferchaud; Céline Peyrard; Joël Léonard; Eric Gréhan; Bruno Mary (Atmosphere, 2020)
Field N2O emissions are a key point in the evaluation of the greenhouse gas benefits of bioenergy crops. The aim of this study was to investigate N2O fluxes from perennial (miscanthus and switchgrass), semi-perennial (fescue and alfalfa) and annual (sorghum and triticale) bioenergy crops and to analyze the effect of the management of perennials (nitrogen fertilization and/or harvest date). Daily N2O emissions were measured quasi-continuously during at least two years in a long-term experiment, using automated chambers, with 2–5 treatments monitored simultaneously. Cumulative N2O emissions from perennials were strongly affected by management practices: fertilized miscanthus harvested early and unfertilized miscanthus harvested late had systematically much lower emissions than fertilized miscanthus harvested late (50, 160 and 1470 g N2O-N ha−1 year−1, respectively). Fertilized perennials often had similar or higher cumulative emissions than semi-perennial or annual crops. Fluxes from perennial and semi-perennial crops were characterized by long periods with low emissions interspersed with short periods with high emissions. Temperature, water-filled pore space and soil nitrates affected daily emissions but their influence varied between crop types. This study shows the complex interaction between crop type, crop management and climate, which results in large variations in N2O fluxes for a given site.